Characterization of Defects by Non-Destructive Impulse Excitation Technique for 3D Printing FDM Polyamide Materials in Bending Mode - Fatima-Ezzahrae Jabri; Imi Ochana; François Ducobu; Rachid El Alaiji; Anthonin Demarbaix (Applied Sciences)
The presented article analyzes the impact of internal defects on the modal responses of polyamide parts subjected to bending. Samples with defects of various sizes (0, 3, 5, 7, and 10 mm) located at the neutral bending line were tested. Modal properties were measured via an acoustic and a vibration sensor, using impulse excitation and fast Fourier transform (FFT) analysis. Modal properties include peak frequency, damping and amplitude. Non-defective samples show lower peak frequency and stronger amplitude for both detectors. Moreover, defects larger than 3 mm have minimal impact on peak frequency. The vibration detector is more sensitive to delamination presented at 7 and 10 mm defects. In addition, elevated peak frequency at 3 mm is the result of local hardening at the defect edge. Moreover, a neutral line position reduces damping when the defect size approaches 5 mm. Conversely, acoustic detectors ignore delamination and reveal lower damping and amplitude at 7 and 10 mm defects. Furthermore, internal sound diffusion from 3 and 5 mm defects enhances air losses and damping. Acoustic detectors only evaluate fault size and position, whereas vibrational detectors may detect local reinforcement and delamination more easily. These results highlight the importance of choosing the right detector according to the location, size, and specific modal characteristics of defects.